2021
DOI: 10.3390/nu13041249
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Deficiencies in Patients with Decompensated Liver Cirrhosis

Abstract: Patients with cirrhosis often develop malnutrition and micronutrient deficiencies, leading to a worse prognosis and increased mortality. Our main goal was to assess the prevalence of micronutrient deficiencies in patients with decompensated cirrhosis. This was a prospective single-center study including 125 consecutive patients hospitalized for acute decompensation of cirrhosis (mostly of alcoholic etiology). A blood test including trace elements and vitamins was performed on admission. The main micronutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 45 publications
0
19
1
1
Order By: Relevance
“…Llibre-Nieto et al noted about 85% prevalence of zinc deficiency; however, none were identified with B12 deficiency similar to our study. Studies have particularly shown that patients in Child-Pugh B or C are at a higher risk of developing zinc deficiency as well as other nutrient and caloric deficits [ 7 , 8 , 10 ]. Overall, there are no set guidelines to date that suggest checking for or monitoring patients with cirrhosis for micronutrient deficiencies in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Llibre-Nieto et al noted about 85% prevalence of zinc deficiency; however, none were identified with B12 deficiency similar to our study. Studies have particularly shown that patients in Child-Pugh B or C are at a higher risk of developing zinc deficiency as well as other nutrient and caloric deficits [ 7 , 8 , 10 ]. Overall, there are no set guidelines to date that suggest checking for or monitoring patients with cirrhosis for micronutrient deficiencies in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have looked at micronutrient deficiencies in liver cirrhosis and methods of effectively identifying those patients that may be at higher risk of these losses [ 7 , 8 ]. Some studies have also shown that educating patients and obtaining appropriate nutritional counseling helped in reducing admissions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Megaloblastic anemia can occur secondary to a micronutrient vitamin B 12 or folate deficiency. 4 , 5 , 6 In patients who consume large quantities of alcohol to the exclusion of more nutritious food may develop nutrient deficiencies. Folate and vitamin B 12 deficiencies impair hematopoiesis and primarily cause a decrease in number of RBCs.…”
Section: Questions/discussion Points Partmentioning
confidence: 99%
“…Tỷ lệ thiếu calci, sắt và phospho tương ứng là 4,6%; 38,8% và 34,4%; có 12,8% bệnh nhân có tình trạng thiếu hụt magie. 6…”
Section: Kết Quảunclassified